The Effect Of The Relationship Between Social Partners On The Performance Of State Corporations In Kenya - Nzioki, Susan (http://ijecm.co.uk, 2016)
The relationship between social partners is expected to enhance performance of State Corporations. Cordial relations would allow groups of divergent interests to recognize each other’s co-existence, while promoting their own distinct views. This study sought to establish whether the relationship between social partners influenced the performance of state corporations in Kenya. The study was done in Nairobi County in Kenya, in Africa. Data was collected from 341 unionized and non-unionized employees of state corporations in the county. A descriptive survey design was adopted. The research instruments used were questionnaire and interview schedule, the former having open-ended and closed-ended Likert scale questions and the later had guiding questions. Data was analyzed quantitatively and qualitatively using Statistical Package of Social Sciences (SPSS). The study found that the relationship between the social partners significantly influenced the performance of state corporations. The study revealed that among various approaches, unions had embraced confrontational approach to agitate for workers' rights. This often forced management to negotiation tables to solve labour issues. The study recommends social partners to appreciate partnership and mutuality approaches to replace the current confrontational/ adversarial approach, which had often interfered with efforts to create industrial harmony.
Keywords: Performance; Equality of partners; Mutuality; Partnership; Adversarial approach; Social actors